PSYCHOMOTOR THERAPY AS A EFFECTIVE METHOD OF ALLEVIATING THE SYMPTOMS OF CHILD’S NON-HARMONIOUS DEVELOPMENT - Gnitecka, Jolanta; Nowak, Agata; Romanowska-Tolloczko, Anna (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: assess the influence of a therapy conducted according to the Belgian School on the psychomotor development of children suffering from developmental dissonance. Material and methods: the studies involved 32 six yrs. old children, having symptoms of developmental dissonance, who qualified for Belgian psychomotor therapy and who came from different areas in Poland. Two measurements of the selected areas of the psychomotor field have been performed using the following tests: MOT 4-6 by R. Zimmer and M. Volkammer; PST 6-8 by S. Naville and A. Weber, B. Mock; WET 3-6 by P. Deimann and U. Kastner-Koller , as well as SCSIT by J. Ayres. The undertaken studies lasted for approximately 6 months and were a pedagogic quasi-experiment in nature. Results: upon the conclusion of experimental factor’s influence i.e. the Belgian psychomotor therapy, it has been observed that in the study pertaining to the psychomotor development, the results obtained by the six-year-old children cease to significantly differ from the values obtained by their peers, displaying no symptoms of dissonance. Conclusion: psychomotor therapy according to the Belgian School is a useful method of alleviating the symptoms of a non-harmonious development of a six-year-old child. A scientific confirmation of the research problem’s significance can facilitate therapist’s work. The results of the research will also contribute to the development of knowledge about diagnosis of developmental dissonance and Belgian psychomotor therapy.